The Pattern of Disaster Communication and Media to Improve Community Alertness in North Aceh Regency - nfn Fauzi; Marhamah Rusdy (Jurnal Pekommas, 2020)
This study aims to analyze the forms of communication carried out and the media used by the North Aceh District Disaster Management Agency in improving community alertness. This research uses descriptive research type, and qualitative research approaches.  Research data obtained through interviews, observations, and documentation studies. Research informants, namely the Local Government, the Head of the North Aceh District Disaster Management Agency, the District Head of Langkahan, the Head of North Aceh SAR, the Head of RRI Lhokseumawe. The results showed that the communication carried out by the North Aceh District Disaster Management Agency was interpersonal communication and mass communication through socialization and simulation about disasters. While the communication media used, namely the mass media both print media and radio media to inform disaster management policies. It also used traditional media as local wisdom namely kentongan. Kentongan media are considered effective when communication tools that use technology do not function.